Association of parental rearing styles with suicidal ideation in Chinese adolescent patients with depression: a large-scale cross-sectional study - Jiacheng Liu; Jiacheng Liu; Chang Cheng; Kamila Edeleva; Zhen Zhao; Liying Yang; Chuanyi Kang; Xiaohong Wang; Na Zhao; Jian Hu (Frontiers in Psychiatry)
BackgroundSuicide is the first cause of death among adolescents globally and has a severe impact on socioeconomic development. Several studies have found that suicide attempts and suicidal ideation (SI) are more likely to occur in adolescents with depression. Previous studies have found that stressful events in early childhood, especially family stress, can influence the occurrence of SI. Chinese parents tend to be more strict and less able to express their emotions, owing to unique national conditions, which may result in more parenting problems. Therefore, our study investigates the risk factors for SI in a large sample of Chinese adolescents with depression.MethodsA total of 1604 adolescent patients with depression were recruited in this study. A self-administered questionnaire collected the clinical and demographic data. SI was assessed by interview. The Egna Minnen Beträffande Uppfostran (EMBU) scale was used to evaluate parental rearing style.ResultsThe study showed that female (OR=1.886, 95%CI:1.502–2.368), sleep (OR=0.798, 95%CI:0.637–0.998), school management (OR=1.179, 95%CI:1.041–1.336), alcohol consumption (OR=1.798, 95%CI:1.304–2.479), child life (OR=1.797, 95%CI:1.457–2.216), maternal interference (OR=1.032, 95%CI:1.015–1.048), paternal emotional warmth (OR=0.975, 95%CI:0.966–0.983) and paternal rejection (OR=1.102, 95%CI:1.063–1.142) were significantly associated with SI.ConclusionsTo recognize SI earlier, physicians and nurses need to pay more attention to those female adolescent depression populations that are experiencing an unhappy childhood, non-democratic school management, alcohol consumption, excessive maternal interference, lack of paternal emotional warmth, and paternal rejection.